PELATIHAN METODE LOGICAL FRAMEWORK ANALYSIS (LFA) DALAM PEMBUATAN BUSINESS PLAN BAGI SISWA SEKOLAH KEJURUAN DI SMK NEGERI 6 BANDAR LAMPUNG - Pratama, Maulana Agung; Mulkhan, Unang (Prosiding Pengabdian FISIP Unila, 2012)
Life skills education  through the program  "Entrepreneurship" or entrepreneurship is  an  applied  education  that students  get the best experience  with  running a  real business  or  directly.   Entrepreneurial activity  is  believed to be  able to provide encouragement,  particularly  to  improve the  quality of life  of students  and generally to  improve the quality of life. This learning  inspires students to have a sense of responsibility and to  individuals who are able  to adapt  to changes  in the era of  globalization by  improving  their skills  to become  competitive  generation without having to  rely on  to  be  an employee or  karyawan.pelatihan entrepreneurship  and  preparation  business proposal   LFA  method  can improve students understanding of  entrepreneurship is  the willingness  and ability  to develop a business plan as outlined in the business plan and manage the business in the form of co-operation in business groups.  This training also motivates participants to have a strong character to be a reliable entrepreneur  to  have  skills  and emotional intelligence. For that,  should  a similar training  is often  done to  foster  entrepreneurial spirit  early on  and improve students knowledge and skills  in business LFA can provide a good mechanism  to develop  a  project  concept  into  a comprehensive  project design documents.  In addition to  foster  life skills,  this training program  also  supports 6 SMK Bandar Lampung  in delivering  and  motivate students  about the  importance of entrepreneurship.  Keywords: life skills,entrepreneurship,logical framework analysis